Arena Simulation Training Guide for Simple Call Center - Razali, Nur Amirah Ilyana; Bareduan, Salleh Ahmad (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Arena simulation software is one of the most used software in the industry, especially in a simple call center system. However, the currently available training guide in the textbook is quite difficult to understand. It will take plenty of time to interpret all the data and info given because these books consist of complex words and explanations. Thus, the objective of this study is to build training guide for a simple call center using Arena simulation. The step-by-step guide to build the simple call center model was successfully built. Next, the study also built a simple simulation model representing the call center process by using that training guideline. Then, the simulation result of the call center model was analyzed. The training guideline was built based on a simple call center problem model in the Simulation with Arena textbook by W. David Kelton. The scopes of this study are to study and applying Arena simulation software to simulate the process flow of the call center. Secondly, the project utilizes the student version of the Arena Simulation software. Besides, the training guide is built based on existing software manual and textbook, and it does not cover complex animations. From the analysis of data, the percentage error of the attempted calls, completed calls and rejected calls between the training guideline model and textbook model was 0 percent. Finally, a new call center model was built using the training guideline. The simulation result of the new call center model showed that there were 681 calls going through the available 20 trunk lines of the call center system. Furthermore, there were 680 attempted calls, 582 completed calls and 98 rejected calls that were successfully recorded during the call center operation which was for 600 minutes. This is in fact an indicator that the training guideline can be a very helpful tool for beginners to learn building an Arena simulation model of a call center operations.